g(-4b)=3(-4b)+7

Simple and best practice solution for g(-4b)=3(-4b)+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for g(-4b)=3(-4b)+7 equation:


Simplifying
g(-4b) = 3(-4b) + 7

Remove parenthesis around (-4b)
g * -4b = 3(-4b) + 7

Reorder the terms for easier multiplication:
-4g * b = 3(-4b) + 7

Multiply g * b
-4bg = 3(-4b) + 7

Remove parenthesis around (-4b)
-4bg = 3 * -4b + 7

Multiply 3 * -4
-4bg = -12b + 7

Reorder the terms:
-4bg = 7 + -12b

Solving
-4bg = 7 + -12b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '12b' to each side of the equation.
12b + -4bg = 7 + -12b + 12b

Combine like terms: -12b + 12b = 0
12b + -4bg = 7 + 0
12b + -4bg = 7

Reorder the terms:
-7 + 12b + -4bg = 7 + -7

Combine like terms: 7 + -7 = 0
-7 + 12b + -4bg = 0

The solution to this equation could not be determined.

See similar equations:

| 2x^3-8x^2-192x=0 | | 6cos+5tan=0 | | 5r+4r-9r= | | 6cisb+5tan=0 | | 2x=-10-2 | | 180=2x+76 | | 180=2x+76+(5x-2) | | 6(3x+5)-5(x-7)=39 | | c=6+5x | | 7x-3=24x+5 | | 7x-3=24x | | 3x+4+4y=16 | | 16=.25b | | b+2.25=5 | | 16=.25 | | 15w*1.25= | | 2(8+6x)+2=4(4+3x)+2x | | 4a^3+12a^2-9a-27=0 | | 45+40a= | | 291.52=8(0.04m+27.70+0.20(27.70)) | | 8h+9=60 | | 21=(8-c)3 | | -70=-2(x+5)+7(4-6x) | | 291.52=8(0.04m+27.70+0.20(27.20)) | | (a+b)+(a-b)-2a=72-72 | | t*5-5=13 | | 4-8(2+5v)+7= | | 21=(8-3) | | 6x+11=-127 | | 15w^2+15w^3= | | 10(x-50)=-80 | | b-17=-3 |

Equations solver categories